Prevalence of myopia and refractive parameters among children and adolescents in Hi-tech District of Chengdu City - Wang, Xiaoqin; Zeng, Liuzhi; Xian, Yiping; Xin, Mei; Shan, Qingqing; Li, Weiye; Lv, Lixia; Liu, Yifeng; Zhang, Rui; Song, Kejian; Tian, Xixi; Guo, Han; et al. (Frontiers in Pediatrics, 2025)
Objective: To analyze the prevalence of myopia among children and adolescents in Chengdu from 2021 to 2023, providing insights for myopia prevention and control. Methods: This study was a school-based cross-sectional study in children and adolescents aged 3–18 years in Hi-tech District of Chengdu City. All the students underwent comprehensive ocular measurement, including uncorrected binocular visual acuity (VA), spherical equivalent error (SER) with noncycloplegic autorefraction, corneal radius (CR), and axial length (AL) . Results: Over the three-year study period from 2021 to 2023, the overall prevalence of myopia was 38.15%, with annual rates of 38.74% in 2021, 38.67% in 2022, and 37.03% in 2023. The prevalence and severity of myopia increased significantly with age (P < 0.001). The prevalence was consistently higher among girls (p<0.001) with 40.17% in 2021, 39.43% in 2022, and 38.33% in 2023 compared to 37.03%, 38.05% and 35.85% among boys in the years, respectively. The myopia prevalence increased with school level (P < 0.001). Mild myopia was the most common (24.47%), followed by moderate (10.77%) and severe myopia (2.91%). The mean SER were -1.72 ± 1.57 D in 2021, -1.32 ± 1.51 D in 2022, and -1.42 ± 1.36 D in 2023 (P < 0.001). AL was stable across most age groups, with mean AL across the overall sample of 23.80 ± 1.02 mm in 2021, 23.79 ± 1.04 mm in 2022, and 23.81 ± 1.04 mm in 2023. Conclusion: Myopic prevalence among children and adolescents in Hi-tech District of Chengdu City decreased from 2021 to 2023. The prevalence increased with age and school level, indicating a need for targeted interventions. Significant changes in spherical equivalent refraction and AL emphasize the importance of early intervention and regular monitoring of myopia for an effective management.